PROBLEMATICS OF LEGAL SYSTEM PROVISION OF HEALTH SERVICES FOR THE COMMUNITY IN THE PERSPECTIV - Harisman Harisman; Faisar Ananda Arfa; Budi Sastra Panjaitan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the problems of the legal system in the implementation of health services for the community in Indonesia. The main focus of this study is on the discrepancy between the applicable regulations and the implementation, which has an impact on the non-optimal health services. Factors such as weak coordination between agencies, limited human resources and health facilities, and lack of supervision over the implementation of regulations are the main obstacles. The research method used is a normative juridical approach by reviewing laws and regulations. The results of the study show the need for regulatory harmonization and strengthening of the supervision system to ensure fair and equitable health services. In addition, improving the quality of human resources and health infrastructure is a crucial factor in realizing optimal health services.